Algorithmic enumeration of regular maps - Connor, Thomas (Ars mathematica contemporanea, 2016)
Given a finite group ?$G$?, we describe an algorithm that enumerates the regular maps having ?$G$? as rotational subgroup, using the knowledge of its table of ordinary characters and its subgroup lattice. To show the efficiency of our algorithm, we use it to compute that, up to isomorphism, there are 796,772 regular maps whose rotational subgroup is the sporadic simple group of O'Nan and Sims.
Keywords: character table; mreža podgrup; O'Nan sporadic simple group; O'Nanova sporadična enostavna grupa; regular map; regularen zemljevid; subgroup lattice; tabela karakterjev